(untitled) (Research, Society and Development, 2021)
Objective: This study aimed to evaluate the prevalence of Noncarious Cervical Lesions (NCCL), Cervical Dentin Hypersensitivity (CDH) and Gingival Recession (GR) and their associated risk factors in athletes. Methodology: A questionnaire was used to obtain basic information. An evaluator clinically examined all subjects. Statistical analysis was performed using Poisson multiple regression with robust variance, and the prevalence ratio and confidence intervals (95%) were calculated. Results: The final sample consisted of 264 athletes of different sports (7285 teeth). The present study found that the type of sport and weekly training time are important factors. Athlete’s ages ranged from 17 to 46 years (mean: 20.33 years). Majority of the athletes were males (90.46%). The teeth most affected by NCCL were the first upper premolars (29.35%), and the prevalence of NCCL increased with age. The prevalence of NCCL, CDH, and GR was 17.42%, 35.35%, and 59.09%, respectively. The linear regression shows that the most important risk factor(s) for NCCL was age, training hours, stress, excessive brushing force and orthodontic appliance; for CDH were age, education, type of sport, training hours and acid diet; and for GR were age, income, education, type of sport and excessive teeth brushing. Conclusion: It must be understood that the presence of all elements are factors capable of destabilizing the athlete’s daily life. Athletes have risk factors that are closely related to the onset and progression of the disease. It is necessary that the dentist knows prevention and minimization measures.